RETRACTED: Glucocorticoids Should Be Used With Caution in Patients With SARS-CoV-2 - Guo, Yong; Chen, Yan; Li, Yingchuan (Frontiers in Medicine, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a global pandemic, and the use of glucocorticoids in clinical practice is controversial. Our clinical experiences with glucocorticoid treatment suggested that, while use was effective in some cases, in other cases, glucocorticoid were ineffective and even resulted in immunosuppression that could lead to deterioration. Therefore, glucocorticoids should be used with caution in patients with SARS-CoV-2.